PERSPEKTIF BISNIS ISLAM - Angga HadeFahrezi; Aprilia Kinanti; M.Raffy Zulkarnain (Cahaya Ilmu Bangsa, 2024)
The Islamic Business Perspective is a framework of views that prioritizes aspects of benefit, justice and social responsibility in business, not just profit-oriented. This article explores the principles and Business Ethics in Islam studies Islamic business perspectives, the foundation of business ethics and the orientation of business ethics. By analyzing case studies and theoretical frameworks, this research highlights the potential of Islamic business models in promoting sustainable development, fairness and justice. The findings contribute to the understanding of Islamic business ethics and their implications for modern business practices. Keyword :Islamic business, sharia principles, orientation of business